2021
DOI: 10.3389/fpsyg.2021.565657
|View full text |Cite|
|
Sign up to set email alerts
|

Coping Behaviors and Psychological Disturbances in Youth Affected by the COVID-19 Health Crisis

Abstract: The COVID-19 pandemic and the quarantine undergone by children in many countries is a stressful situation about which little is known to date. Children and adolescents' behaviors to cope with home confinement may be associated with their emotional welfare. The objectives of this study were: (1) to examine the coping strategies used out by children and adolescents during the COVID-19 health crisis, (2) to analyze the differences in these behaviors in three countries, and (3) to examine the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 33 publications
3
53
0
3
Order By: Relevance
“…In the Spanish sample, no significant differences were found between the three measurements, except for anxiety, which was more likely five weeks after the confinement than at the first assessment, and decreased from the second to the third assessment. Anxiety symptoms are commonly reported manifestations related to children’s stress during the COVID-19 pandemic [ 5 , 6 , 10 , 16 ]. In line with these findings, it is not surprising that, in the present study, the level of Spanish children with anxiety symptoms increased after five weeks of being confined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Spanish sample, no significant differences were found between the three measurements, except for anxiety, which was more likely five weeks after the confinement than at the first assessment, and decreased from the second to the third assessment. Anxiety symptoms are commonly reported manifestations related to children’s stress during the COVID-19 pandemic [ 5 , 6 , 10 , 16 ]. In line with these findings, it is not surprising that, in the present study, the level of Spanish children with anxiety symptoms increased after five weeks of being confined.…”
Section: Discussionmentioning
confidence: 99%
“…Parents had to deal with many stressors during the lockdown, such as taking care of their children´s learning, working from home, or managing the household [ 1 3 ]. Children also had to face the stress derived from the pandemic [ 4 6 ]. School closure changed children’s academic routines, and the social distance limited their relationships to indoors.…”
Section: Introductionmentioning
confidence: 99%
“…There is mixed evidence for the main effect of spending time with friends on internalizing problems: Spending more time with peers has been linked to a decrease in social anxiety one year later, even when controlling for prior social anxiety (Nelemans et al., 2016 ). Yet, a cross‐sectional study found that adolescents were particularly at risk to experience depressive symptoms if they spent more time with friends during the COVID‐19 crisis (Ellis, Dumas, & Forbes, 2020 ), possibly because they use more emotion‐oriented coping strategies, such as co‐rumination (Starr, 2015 ), that have been associated with internalizing symptoms (Duan et al., 2020 ; Orgilés et al., 2021 ).…”
Section: The Role Of Time Spent With Friends In Internalizing Symptomsmentioning
confidence: 99%
“…Most research examining adolescent coping during the pandemic has been conducted in Europe or Asia; therefore, cultural differences in the way a young person copes may exist. For example, Orgilés et al [ 47 ] examined coping behaviors among youths in three European countries, finding that strategies varied by country. Scholars have noted that coping with extreme stressors varies by culture; however, these differences have yet to be extensively studied [ 48 ].…”
Section: Discussionmentioning
confidence: 99%